A scoping review on the use and usefulness of online symptom checkers and triage systems: How to proceed? - Pairon, Anthony; Philips, Hilde; Verhoeven, Veronique (Frontiers in Medicine, 2023)
Background Patients are increasingly turning to the Internet for health information. Numerous online symptom checkers and digital triage tools are currently available to the general public in an effort to meet this need, simultaneously acting as a demand management strategy to aid the overburdened health care system. The implementation of these services requires an evidence-based approach, warranting a review of the available literature on this rapidly evolving topic. Objective This scoping review aims to provide an overview of the current state of the art and identify research gaps through an analysis of the strengths and weaknesses of the presently available literature. Methods A systematic search strategy was formed and applied to six databases: Cochrane library, NICE, DARE, NIHR, Pubmed, and Web of Science. Data extraction was performed by two researchers according to a pre-established data charting methodology allowing for a thematic analysis of the results. Results A total of 10,250 articles were identified, and 28 publications were found eligible for inclusion. Users of these tools are often younger, female, more highly educated and technologically literate, potentially impacting digital divide and health equity. Triage algorithms remain risk-averse, which causes challenges for their accuracy. Recent evolutions in algorithms have varying degrees of success. Results on impact are highly variable, with potential effects on demand, accessibility of care, health literacy and syndromic surveillance. Both patients and healthcare providers are generally positive about the technology and seem amenable to the advice given, but there are still improvements to be made toward a more patient-centered approach. The significant heterogeneity across studies and triage systems remains the primary challenge for the field, limiting transferability of findings. Conclusion Current evidence included in this review is characterized by significant variability in study design and outcomes, highlighting the significant challenges for future research. An evolution toward more homogeneous methodologies, studies tailored to the intended setting, regulation and standardization of evaluations, and a patient-centered approach could benefit the field.